A Tutorial on Core Lexicon: Development, Use, and Application - Kim, Hana; Wright, Heather Harris (Seminars in Speech and Language, 2020)
Evidence suggests that discourse-level assessment in aphasia should be implemented within clinical settings. However, existing discourse measures that are time and labor intensive in process prevent speech-language pathologists from applying such measures to their clinical practices. This article provides an overview of a lexicon-based analysis (core lexicon measure) that recently was developed and investigated for clinical usability. A new approach to core lexicon measures provides a simple scoring method with short instructions, which may be practical and time efficient for assessment and management of persons with aphasia. The article concludes with suggestions for clinical application and implementation.
Keywords: core lexicon; discourse analysis; aphasia